The Rise of the Agricultural Welfare State : Institutions and Interest Group Power in the United States, France, and Japan - Sheingate, Adam D., 1969- (Book collections on Project MUSE., 2001)
"This study not only puts a new spin on agricultural policy, but also makes a strong case for the broader claim that the relatively decentralized American political system is actually less prone to capture and rule by subgovernments than the more centralized political systems found in France and Japan. Sheingate's historical, comparative approach also demonstrates, in a widely useful way, how past institutional developments shape current policies and options."--Jacket.